Pengaruh Self-Efficacy Dan Grit terhadap Work Engagement (We) Yang Dimoderasi oleh Perceived Organizational Support (Studi pada Tenaga Perawat di RSUD Sambas) - Helixyap Helixyap; Rian Andriani; Yen Efawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Nurses play a vital role in providing healthcare services in hospitals as they are directly involved in patient care 24 hours a day. To provide optimal and professional services, nurses must possess high work engagement toward the hospital. High turnover rates are often caused by low work engagement, influenced by factors such as low self-efficacy and grit. These issues are expected to be addressed through Perceived Organizational Support (POS) provided by the organization. This study aims to determine and analyze the influence of self-efficacy and grit on work engagement, with Perceived Organizational Support (POS) acting as a moderating variable. This study aims to determine and analyze the influence of self-efficacy and grit on work engagement, with Perceived Organizational Support (POS) acting as a moderating variable. This research follows a quantitative approach. The sample was selected using a purposive sampling technique, resulting in 131 respondents who met the inclusion criteria. Statistical instruments used for data analysis included Moderated Regression Analysis (MRA), preceded by validity, reliability, and normality tests. The results of the study indicate that self-efficacy and grit have an influence on work engagement, and this relationship is moderated by Perceived Organizational Support (POS).